Whole-genome sequencing reveals transmission of gonococcal antibiotic resistance among men who have sex with men: an observational study. (15th December 2017) - Kwong, Jason C; Chow, Eric P F; Stevens, Kerrie; Stinear, Timothy P; Seemann, Torsten; Fairley, Christopher K; Chen, Marcus Y; Howden, Benjamin P
Abstract : Objectives: Drug-resistant Neisseria gonorrhoeae are now a global public health threat. Direct transmission of antibiotic-resistant gonococci between individuals has been proposed as a driver for the increased transmission of resistance, but direct evidence of such transmission is limited. Whole-genome sequencing (WGS) has superior resolution to investigate outbreaks and disease transmission compared with traditional molecular typing methods such as multilocus sequence typing (MLST) and N. gonorrhoeae multiantigen sequence (NG-MAST). We therefore aimed to systematically investigate the transmission of N. gonorrhoeae between men in sexual partnerships using WGS to compare isolates and their resistance to antibiotics at a genome level. Methods: 458 couples from a large prospective cohort of men who have sex with men (MSM) tested for gonorrhoea together between 2005 and 2014 were included, and WGS was conducted on all isolates from couples where both men were culture-positive for N. gonorrhoeae . Resistance-determining sequences were identified from genome assemblies, and comparison of isolates between and within individuals was performed by pairwise single nucleotide polymorphism and pangenome comparisons, and in silico predictions of NG-MAST and MLST. Results: For 33 of 34 (97%; 95% CI 85% to 100%) couples where both partners were positive for gonorrhoea, the resistance-determining genes and mutations were identical in isolates from each partner (94 isolates in total). Resistance determinants in isolates from 23 of 23 (100%; 95% CI 86% to 100%) men with multisite infections were also identical within an individual. These partner and within-host isolates were indistinguishable by NG-MAST, MLST and whole genomic comparisons. Conclusions: These data support the transmission of antibiotic-resistant strains between sexual partners as a key driver of resistance rates in gonorrhoea among MSM. This improved understanding of the transmission dynamics of N. gonorrhoeae between sexual partners will inform treatment and prevention guidelines.